Peran Brush Border Membrane Vesicle (BBMV) dalam proses infeksi Baculovirus - Arman Wijonarko (Jurnal Entomologi Indonesia, 2005)
The Role of Brush Border Membrane Vesicle (BBMV) in The Baculovirus Infection. Although baculovirus becoming recognized as potential important agents for control pests, there are several important obstacles for commercial use insecticide. One important obstacle is their narrow host. The other obstacle is due to its development resistance, the phenomenon whereby host larvae become progressively more resistant to fatal infection as they age within and among instars. From practical stand point, this phenomenon impacts the effectiveness of baculovirus control programs against agricultural and forest insect pests that is necessary to adjust application levels in the response to the demography of the target insect population. Purified columnar cells derived from midgut of armyworm Pseudaletia separata was used for fusion assay and observed by means of fluorescence assay based on self-quenching of octadecylrhodamine B chloride (R18). Confocal microscopy of the columnar cells that had been combined with labeled virus showed that the fluorescence appeared on the apical part in the brush border membrane, this indicated that there was fusion between virus and the cells. Two dimensional SDS-PAGE and immunobloting assay confirmed that the receptor exist within the columnar cells.